Designed mini protein 20 mimicking uricase encapsulated in ZIF-8 as nanozyme biosensor for uric acid detection - Abdul Aziz, Siti Fatimah Nur; Salleh, Abu Bakar; Ashari, Siti Efliza; Normi, Yahaya M.; Yusof, Nor Azah; Ahmad, Shahrul Ainliah Alang (MDPI, 2022)
This work presents the use of encapsulated mini protein 20 mimicking uricase (mp20)-zeolitic imidazolate framework-8 (ZIF-8) as a bioreceptor for the development of a nanozyme-based electrochemical biosensor for uric acid detection. The electrochemical performance of the biofunctionalized mp20@ZIF-8 on the reduced graphene oxide/screen-printed carbon electrode (rGO/SPCE) was investigated by optimizing operating parameters such as pH, deposition potential, and deposition time using a central composite design-response surface methodology (CCD-RSM). The quadratic regression model was developed to correlate the combination of each variable to the oxidation current density as a response. A significant effect on current response was observed under optimized conditions of pH of 7.4 at −0.35 V deposition potential and 56.56 s deposition time, with p < 0.05 for each interacted factor. The obtained coefficient of determination (R2) value of 0.9992 indicated good agreement with the experimental finding. The developed nanozyme biosensor (mp20@ZIF-8/rGO/SPCE) exhibited high selectivity in the presence of the same fold concentration of interfering species with a detection limit of 0.27 μM, over a concentration range of 1 to 34 μM. The practicality of the tailored biosensor in monitoring uric acid in human serum and urine samples was validated with high-performance liquid chromatography (HPLC) and a commercial uric acid meter. Hence, nanozyme-based is a promising platform that offers a rapid, sensitive, selective, and low-cost biosensor for the non-enzymatic detection of uric acid in biological samples.